1999
DOI: 10.1098/rspb.1999.0930
|View full text |Cite
|
Sign up to set email alerts
|

Birth order and fluctuating asymmetry: a first look

Abstract: We investigated the hypothesis that maternal immunoreactivity to male-speci¢c features of the foetus can increase developmental instability. We predicted that the participants' number of older brothers would be positively related to the £uctuating asymmetry of ten bilateral morphological traits. The participants were 40 adult male psychiatric patients and 31 adult male hospital employees. Consistent with the hypothesis, the participants' number of older brothersöbut not number of older sisters, younger brother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
1
18
1
Order By: Relevance
“…Fourth, fraternal birth order was not associated with FA in our study as previously reported (Lalumiere et al, 1999). The association between birth order and FA has been considered to result from maternal immunoreactivity to male-specific features of the fetus (Lalumiere et al, 1999).…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Fourth, fraternal birth order was not associated with FA in our study as previously reported (Lalumiere et al, 1999). The association between birth order and FA has been considered to result from maternal immunoreactivity to male-specific features of the fetus (Lalumiere et al, 1999).…”
Section: Discussioncontrasting
confidence: 41%
“…The association between birth order and FA has been considered to result from maternal immunoreactivity to male-specific features of the fetus (Lalumiere et al, 1999). Maternal immunoreactivity, in turn, would have more deleterious effects on the males because male fetuses ''are more antigenic'' to the mother than female fetuses (Gualtieri and Hicks, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, none of the studied factors exhibited an association with the extent of FA (except for signed right-to-left scores of centroid size in non-fused greater horns which is likely due to sampling bias). This applies in particular to an individual's sex, which suggests that both sexes are susceptible to the same extent and that the hyoid bone may be resistant to the so-called "male-specific maternal immunoreactivity", which assumes that a mother's immune response to a male foetus increases developmental instability (Lalumière et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Among humans, increased FA has been linked to several specific stresses, such as maternal obesity, maternal nicotine, and alcohol use (Kieser, 1992;Kieser, Groeneveld, & Da Silva, 1997), severe malnutrition during prenatal development (Kieser & Groeneveld, 1988), and exposure to a maternal immune response evoked by multiple exposures to male fetuses (Lalumière, Grant, & Rice, 1999). One outcome in animals exposed to prenatal stress is a modification of sexual behavior with sex-atypical behaviors becoming more common (Ward, 1972).…”
Section: Introductionmentioning
confidence: 99%